2000
DOI: 10.1046/j.1523-1739.2000.99329.x
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking Tropical Forest Conservation: Perils in Parks

Abstract: According to some conservationists, large, pristine, uninhabited parks are the defining criterion of success in conserving tropical forests. They argue that human residents in tropical forests inevitably deplete populations of large animals through hunting, which triggers a chain reaction of ecological events that greatly diminish the conservation value of these forests. Hence, they believe that removal of people from tropical forests is an essential step in the creation of successful parks and in the conserva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
169
0
20

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 291 publications
(189 citation statements)
references
References 18 publications
(18 reference statements)
0
169
0
20
Order By: Relevance
“…Community co-management must be applied in the process of reserve management. Many studies have indicated that management plans and management activities have been carried out successfully in many reserves because of the participation of local communities (Borrie et al 1998;Hayes 2006;Schwartzman et al 2000). Thirdly, improvement of living standards in surrounding communities is an important component of the resolution of conflicts between reserves and their surrounding communities (Jim and Xu 2002;Zhang et al 2006), and also an important criterion for nature-reserve management.…”
Section: Recommendationsmentioning
confidence: 99%
“…Community co-management must be applied in the process of reserve management. Many studies have indicated that management plans and management activities have been carried out successfully in many reserves because of the participation of local communities (Borrie et al 1998;Hayes 2006;Schwartzman et al 2000). Thirdly, improvement of living standards in surrounding communities is an important component of the resolution of conflicts between reserves and their surrounding communities (Jim and Xu 2002;Zhang et al 2006), and also an important criterion for nature-reserve management.…”
Section: Recommendationsmentioning
confidence: 99%
“…It is not by a chance that some native populations remain near the last fragments of Brazilian Atlantic Forest, often overlapping conservation areas. The conservationist debate over areas free from people versus areas where conservation and use could be coupled is not a new one (Zube & Busch 1990;Schimink et al 1992;Kemf 1993;Schwartzman et al 2000;Peres & Zimmerman 2001). Ethnobotany studies can contribute to this debate, analyzing how local people identify and use the forest resources, and which areas and which species are used most intensively (La Torre-Cuadros & Islebe 2003; Dalle & Potvin 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Emerging partnerships between faith groups and conservation science present another powerful opportunity (Dudley et al 2006). Policies emphasizing political empowerment, self-governance and territorial control at the grass-roots level have the potential to provide a solid platform from which communities can play a central role in biodiversity conservation at the same time as retaining their own cultural distinctiveness and connectedness to the land (Colchester 2000;Schwartzman et al 2000;Peres & Zimmerman 2001;Heckenberger 2004;Athayde et al 2007).…”
Section: Better Integration For the Futurementioning
confidence: 99%